Revenge, Coloniality, and Hegelian Justice: Experiencing Geopolitics in Sub-Saharan Fiction - Uwe, Christian (Dalhousie French Studies, 2021)
In his Outlines of a Philosophy of Right, Hegel contends that revenge is just in its content but wrong in its form. In other words, it is justified in its pursuit of recognition but wrong in resorting to acts of subjective will instead of mediation through state justice, which, he argues, is founded in a rational and objective expression of collective will. While Hegel’s argument may hold in cases of conflicts between individual subjects, it is harder to sustain when the wrong is committed by supra-individual entities (States, financial institutions) particularly in (neo)colonial contexts. In light of this asymmetrical complication, I seek to revisit the conception of justice associated with the Hegelian idea of the State. I do so by looking at four contemporary francophone novels in which episodes of individual revenge are construed as provocative indices that allow me to uncover the wrong in its asymmetrical setting, that is, to see and analyze offense as the personal, individual and intimately lived effect of a (geo)political wrong inflicted by (neo)colonialism. Ultimately, the assumption of State rationality is significantly qualified due to the influence of capitalist market forces and national sentiment.